2017
DOI: 10.1097/tp.0000000000001635
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for an Expanded Use of Kidneys From Elderly Donors

Abstract: The old-for-old allocation policy used for kidney transplantation (KT) has confirmed the survival benefit compared to remaining listed on dialysis. Shortage of standard donors has stimulated the development of strategies aimed to expand acceptance criteria, particularly of kidneys from elderly donors. We have systematically reviewed the literature on those different strategies. In addition to the review of outcomes of expanded criteria donor or advanced age kidneys, we assessed the value of the Kidney Donor Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 193 publications
(339 reference statements)
2
45
0
3
Order By: Relevance
“…Our study also shows that the use of a relatively low threshold (RS ≤ 4) appears to be safe for single kidney transplantation and identifies good organs from donors with several risk factors that would otherwise be rejected. Of importance, dual kidney transplantation in ECD donors has recently been reported not offer greater advantages , while our results demonstrate the good functioning of single kidney transplantation with marginal kidneys.…”
Section: Discussionsupporting
confidence: 46%
“…Our study also shows that the use of a relatively low threshold (RS ≤ 4) appears to be safe for single kidney transplantation and identifies good organs from donors with several risk factors that would otherwise be rejected. Of importance, dual kidney transplantation in ECD donors has recently been reported not offer greater advantages , while our results demonstrate the good functioning of single kidney transplantation with marginal kidneys.…”
Section: Discussionsupporting
confidence: 46%
“…Nonetheless, it is possible that the beneficial effect on survival of KT is not so robust in patients aged >70 years, diabetics and those with chronic obstructive pulmonary disease, as previously reported by Perez-Saez et al [68], suggesting that this benefit may not be extrapolatable to older patients. However, a later systematic review carried out by these same authors showed an overall better patient survival at the fifth year post-transplantation in elderly KT recipients compared with age-matched waitlisted patients [69]. …”
Section: Comparing Mortality Risk On Waiting-list Versus Post-transplmentioning
confidence: 99%
“…Currently, only limited data are available to predict progression to chronic kidney disease in patients who receive a kidney transplant. The recent evolution in recipient demographics and expansion of the donor pool have introduced several important variables that may contribute to the lack of improvement in longterm allograft survival but may be better matched with predicted patient survival [4][5][6][7]. Although the changes in the kidney allocation scoring system have led to presumed improved equity in organ availability for disadvantaged recipients, the transplant community is in need of an objective measure to aid in determining which patients are at the highest risk for graft failure [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%